Contested Properties: Peoples, Plants and Politics in Post-Apartheid South Africa - Rutert, Britta (transcript, 2020)
This book deals with the values of medicinal plants and associated knowledge(s) in the field of bioprospecting in post-apartheid South Africa. Bioprospecting, the use of genetic or biological resources for commercial purposes, is a profit-oriented enterprise facing new challenges with the rise of human rights and biodiversity politics. This new situation has led to claims for political leverage made by indigenous communities, as well as to claims for national and local cultural identity and heritage. The picture presented here contributes to the widely discussed yet so far unresolved question of how to appropriately share benefits, and how to protect indigenous knowledge in this field.